Da disgestibilidade "in vitro" de algumas forrageiras tropicais - da Silva, Dirceu Jorge; Campos, Joaquim; H Conrad, Joseph (Revista Ceres, 2024)
The present study began with the cutting of 8 forages; Perennial Soybean (Glycine javanica); Centrosema (Centrosema pubescens); Elephant Grass-Napier (Pennisetum purpureum); Guatemala Grass (Tripsacum fasciculatum); Sempre Verde Grass (Panicum maximum); Jaragua Grass (Hyparrhenia rufa) Molasses Grass (Mellinis minutiflora); Pangola Grass (Digitaria decumbens). Each forage, after the firstcutting, was respectively collected when completing 30, 60 and 90 days of age, Initially dry matter was determinethden cellulose; before and after fermentation "in vitro" with rumen liquor.